Introduction to Materials for Advanced Energy Systems - Tong, Colin (Springer International Publishing : Imprint: Springer, 2019)
This first of its kind text enables today's students to understand current and future energy challenges, to acquire skills for selecting and using materials and manufacturing processes in the design of energy systems, and to develop a cross-functional approach to materials, mechanics, electronics and processes of energy production. While taking economic and regulatory aspects into account, this textbook provides a comprehensive introduction to the range of materials used for advanced energy systems, including fossil, nuclear, solar, bio, wind, geothermal, ocean and hydropower, hydrogen, and nuclear, as well as thermal energy storage and electrochemical storage in fuel cells. A separate chapter is devoted to emerging energy harvesting systems. Integrated coverage includes the application of scientific and engineering principles to materials that enable different types of energy systems. Properties, performance, modeling, fabrication, characterization and application of structural,functional and hybrid materials are described for each energy system. Readers will appreciate the complex relationships among materials selection, optimizing design, and component operating conditions in each energy system. Research and development trends of novel emerging materials for future hybrid energy systems are also considered. Each chapter is basically a self-contained unit, easily enabling instructors to adapt the book for coursework. This textbook is suitable for students in science and engineering who seek to obtain a comprehensive understanding of different energy processes, and how materials enable energy harvesting, conversion, and storage. In setting forth the latest advances and new frontiers of research, the text also serves as a comprehensive reference on energy materials for experienced materials scientists, engineers, and physicists. Includes pedagogical features such as in-depth side bars, worked-out and end-of- chapter exercises, and many references to further reading Provides comprehensive coverage of materials-based solutions for major and emerging energy systems Brings together diverse subject matter by integrating theory with engaging insights .